Clinical and transcriptional recovery profiles in pediatric and adult multiple sclerosis patients. Issue 1 (16th November 2020) - Menascu, Shay; Khavkin, Yulia; Zilkha‐Falb, Rina; Dolev, Mark; Magalashvili, David; Achiron, Anat; Gurevich, Michael
Abstract: Objective: To determine whether pediatric‐onset multiple sclerosis (POMS) and adults‐onset multiple sclerosis (AOMS) patients are different in initial disease severity and recovery and to investigate the associations with peripheral blood mononuclear cells (PBMCs) transcriptional profiles. Methods: Clinical and radiological severity of first and second relapses and 6‐month recovery were analyzed in 2153 multiple sclerosis (MS) patients and compared between POMS (onset at 8–18years old) and AOMS (onset at 19–40 years old) patients. PBMCs transcriptomes of 15 POMS and 15 gender‐matched AOMS patients were analyzed 6 months after the first relapse and compared to 55 age‐matched healthy controls. Differentially Expressed Genes (DEGs) with a false discovery rate ≤ 10% were evaluated using the Partek software. Results: POMS had increased Expanded Disability Status Scale (EDSS) score at first and second relapses, higher brain gadolinium‐enhancing T1‐lesions volume at first relapse, and more complete recovery after both relapses compared to AOMS. POMS patients, who recovered completely from the first relapse, were characterized by 19 DEGs that were mainly related to suppression of antigen presentation. Six upstream regulators of these genes were differentially expressed between pediatric and adult healthy controls. POMS patients, who showed no recovery from the first relapse, were characterized by 28 DEGs that were mainly associated with B‐cell activation. Five upstream regulators of these genes were differentially expressed between pediatric and adult healthy controls. Interpretation: POMS patients may have more severe first and second relapses than AOMS. However, most often, POMS have better recovery that may be attributed to PBMCs age‐related transcriptional profiles associated with antigen presentation and B‐cell activation.